THE MUTUAL IMPORTANCE OF THE PUNCTUATION DEPARTMENT AND THE NATIONAL CORPUS (American Journal of Pedagogical and Educational Research, 2025)
This article provides an overview of national corpora and punctuation and explains their interrelationship. It is known that in the literature on punctuation, punctuation marks are classified according to their general characteristics - place of use, method of use, structure, function. The article highlights the importance of punctuation marks in the national corpus.